Meta-Analysis: Association Between Hypoglycemia and Serious Adverse Events in Older Patients Treated With Glucose-Lowering Agents - Mattishent, Katharina; Loke, Yoon K. (Frontiers in Endocrinology, 2021)
Aims: We conducted a meta-analysis of serious adverse events (dementia, macro- and micro-vascular events, falls and fractures, death) associated with hypoglycemia in older patients treated with glucose lowering drugs. Materials and Methods: Meta-analysis of studies reporting on hypoglycemia and adverse events. The search included studies from two previously published systematic reviews, and an updated search of MEDLINE and EMBASE from April 2014 to November 2019. We assessed study validity based on ascertainment of hypoglycemia, adverse events and adjustment for confounders, and conducted a random effects meta-analyses, assessing heterogeneity using the I2 statistic. Results: We included 44 studies involving 2,507,434 participants. Most of the studies used adjusted analysis for confounders and hypoglycaemic events were typically identified based on healthcare databases (severe events). Hypoglycemia was associated with increased likelihood of death in a meta-analysis of eighteen studies, pooled OR 2.02 (95% Confidence Interval 1.75 to 2.32). Studies assessing mortality signal a time-response relationship with a higher risk of adverse events occurring within the first 90 days after hypoglycemia. Our meta-analysis of nine studies demonstrated that hypoglycaemic episodes were associated with dementia – pooled OR 1.50 (95% CI 1.29 to 1.74). Our updated meta-analysis of nineteen studies confirms previously reported associations with macrovascular complications, pooled OR 1.81 (95% CI 1.70 to 1.94), and microvascular complications (two studies) pooled OR 1.77 (95% CI 1.49 to 2.10). Similarly, our updated meta-analysis of six studies confirmed an association between hypoglycemia and falls and fractures, pooled OR 1.78 (95% CI 1.44 to 2.21) and 1.68 (95% CI 1.37 to 2.07) respectively. Conclusion: This updated meta-analysis confirms previously reported concerns of serious harm following hypoglycemia, especially in the immediate time period after a hypoglycaemic event. Avoidance of hypoglycaemic episodes should be a priority in this vulnerable population.